2003
DOI: 10.1029/2002gl016268
|View full text |Cite
|
Sign up to set email alerts
|

Presunrise ion temperature enhancement observed at 600 km low‐ and mid‐latitude ionosphere

Abstract: [1] The quiet-time low-and mid-latitude topside ionospheric ion temperature measured with ROCSAT-1/IPEI instrument is studied for local time, longitudinal, latitudinal, and seasonal variations for the solar maximum year of 2000. The statistical result shows two significant observations at the presunrise sector. Namely, the earliest presunrise ion temperature increase at 600 km low-and mid-latitude ionosphere always starts in the winter hemisphere for both summer and winter seasons; and the strongest presunrise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 12 publications
3
37
0
Order By: Relevance
“…That is, at higher altitudes (above ∼300 km), the photoelectron heat not only comes from local hemisphere but also from the conjugate hemisphere. Some studies have shown presunrise plasma temperature enhancements was contributed to by the photoelectron heating from the conjugate sunlit region (Evans, 1973;Peterson et al, 1977;Chao et al, 2003, Zhang et al, 2004. During a solar eclipse, photoelectrons in the eclipse region are reduced largely at totality, then in its conjugate region the inflow photoelectron flux from the eclipse region will decrease a lot, which results in a large decrease in electron temperature in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, at higher altitudes (above ∼300 km), the photoelectron heat not only comes from local hemisphere but also from the conjugate hemisphere. Some studies have shown presunrise plasma temperature enhancements was contributed to by the photoelectron heating from the conjugate sunlit region (Evans, 1973;Peterson et al, 1977;Chao et al, 2003, Zhang et al, 2004. During a solar eclipse, photoelectrons in the eclipse region are reduced largely at totality, then in its conjugate region the inflow photoelectron flux from the eclipse region will decrease a lot, which results in a large decrease in electron temperature in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The ionospheric responses to a solar eclipse have been studied extensively with various methods, such as the Faraday rotation measurement, ionosonde network, incoherent scatter radar (ISR), Global Positioning System (GPS), and satellite measurements (e.g., Salah et al, 1986;Tsai and Liu, Correspondence to: L. Liu (liul@mail.iggcas.ac.cn) 1999; Afraimovich et al, 1998;Davis et al, 2000) as well as theoretical modelling (Stubbe, 1970;Müller-Wodarg et al, 1998;Boitman et al, 1999;Le et al, 2008a). These studies have shown that there is an almost consistent behavior at low altitudes where there are distinct depletions in electron concentration and electron temperature during solar eclipses.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies on the ionospheric response to solar eclipse on the basis of the numerical simulations in the past (e.g. Stubbe, 1970;Roble et al, 1986;Müller-Wodarg et al, 1998;Boitman et al, 1999;Liu et al, 1999;Korenkov et al, 2003a, b). However, for the variations of solar radiation during a solar eclipse, they only considered the occultation of the photosphere, i.e.…”
Section: Ionospheric Model and Solar Radiation During An Eclipsementioning
confidence: 99%
“…In the past, there have been some studies on the ionospheric response to solar eclipses on the basis of numerical simulations (e.g. Stubbe, 1970;Roble et al, 1986;Müller-Wodarg et al, 1998;Boitman et al, 1999;Liu et al, 1999;Korenkov et al, 2003aKorenkov et al, , 2003b. However, they only considered the occultation of the photosphere being shielded by the Moon for variations in solar radiation during a solar eclipse.…”
Section: Introductionmentioning
confidence: 99%
“…Ion parameter global distributions were derived from the ROCSAT-1 observation and revealed many unique features in various local time sectors, like pre-dawn heating (Chao et al 2003b(Chao et al , 2010, ion temperature crests in the morning hours (Chao et al 2004), and movements of the temperature crests in the afternoon sector , etc. However, lack of electron temperature measurement in the ROCSAT-1 satellite, many temperature features could not be fully understood.…”
Section: Background Ionospherementioning
confidence: 99%